1999
DOI: 10.1002/(sici)1097-0215(19990105)80:1<145::aid-ijc26>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Frequent deregulation ofp16 and thep16/G1 cell cycle-regulatory pathway in neuroblastoma

Abstract: Alterations of the p16 gene in neuroblastoma are very rare. Pronounced expression of p16 at both the transcript and protein levels, however, was observed in 7 of 19 (39%) neuroblastoma cell lines and 2 of 6 (33%) primary neuroblastoma samples. As p16 expression is tightly controlled in a feedback loop with Rb, we investigated the possibility that changes in p16 expression were reflective of alterations of the downstream components in the G1 regulatory pathway. Two cell lines and one primary sample highly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Several attempts have been carried out to link the occurrence of p16 INK4A /p14 ARF /p15 INK4B alterations with prognosis or disease progression (reviewed in Drexler, 1998;Tsihlias et al, 1999). Whereas many studies show p16 INK4A deletions as an independent risk factor for a poor outcome in childhood ALL (Okuda et al, 1995;Zhou et al, 1997;Yamada et al, 1997;Kees et al, 1997;Tsihlias et al, 1999;Moreno et al, 2000;Ramakers-van Woerden et al, 2001;Carter et al, 2001) or as a marker for disease progression (Diccianni et al, 1994;Ohnishi et al, 1996;Kees et al, Maloney et al, 1999;Carter et al, 2001), one large study (Rubnitz et al, 1997) found no correlation between p16 INK4A deletion and either the survival or relapse rate in 155 ALL patients. Only a few studies to date have attempted to correlate p15 INK4B promoter methylation with clinical outcome.…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been carried out to link the occurrence of p16 INK4A /p14 ARF /p15 INK4B alterations with prognosis or disease progression (reviewed in Drexler, 1998;Tsihlias et al, 1999). Whereas many studies show p16 INK4A deletions as an independent risk factor for a poor outcome in childhood ALL (Okuda et al, 1995;Zhou et al, 1997;Yamada et al, 1997;Kees et al, 1997;Tsihlias et al, 1999;Moreno et al, 2000;Ramakers-van Woerden et al, 2001;Carter et al, 2001) or as a marker for disease progression (Diccianni et al, 1994;Ohnishi et al, 1996;Kees et al, Maloney et al, 1999;Carter et al, 2001), one large study (Rubnitz et al, 1997) found no correlation between p16 INK4A deletion and either the survival or relapse rate in 155 ALL patients. Only a few studies to date have attempted to correlate p15 INK4B promoter methylation with clinical outcome.…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
“…Nevertheless, presence of p53 mutation was correlated with a poor clinical outcome (Marks et al, 1997;Kornblau et al, 1998). An increased incidence of p53 mutations occurs in relapsed childhood ALL (Marks et al, 1997), childhood T-ALL Diccianni et al, 1994;Kawamura et al, 1999) and childhood ALL carrying the t(1;19) translocation (Kawamura et al, 1995). However, two studies did not ®nd a correlation between p53 mutations and outcome in adult ALL (Fenaux et al, 1992a;Tsai et al, 1996).…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
“…INK4A (42,43). This observation may be explained by the overexpression in neuroblastomas of Id2, which has been suggested to sequester and inactivate pRb and thus bypass p16…”
Section: Repression Of Mycn By Tgf-␤ Requires the E2f-binding Sites-tmentioning
confidence: 99%
“…Thus, it is unlikely that mutations in the regions studied would be missed in specimens composed predominantly of leukemic cells, as was the case in the present study. We analysed p53 exons 4 ± 8 and the¯anking introns because the p53 mutations in leukemias that have been described occur within this region (Diccianni et al, 1994 , 1992a,b, 1994Greenblatt et al, 1994;Kawamura et al, 1995;Prokocimer and Rotter, 1994;Wada et al, 1993). Thus, the data from this study would suggest that p53 mutations are infrequent in leukemias with MLL gene translocations.…”
mentioning
confidence: 99%
“…Combined studies in the literature indicate that p53 gene mutations are also rare in ALL, on the order of only 2% at initial presentation (Felix et al, 1992b;Kawamura et al, 1995;Wada et al, 1993). In B-lineage ALL with the t(1;19) chromosomal translocation and in T-cell ALL, p53 mutations are acquired at relapse (Diccianni et al, 1994;Kawamura et al, 1995). MDM2 gene overexpression without ampli®cation has been suggested as an alternative mechanism of wild-type p53 inactivation in childhood ALL, but karyotypes were not described (Marks et al, 1997;Zhou et al, 1995).…”
mentioning
confidence: 99%